Breaking Away from the Binary: Do Drag Queens Adopt a Female Style or a Distinct Drag Queen Speech? - Essing, Hannah (Satura, 2020)
RuPaul's Drag Race [RPDR] is an American reality TV show that aired for the first time in 2009. In typical America's Next Top Model demeanour contestants are competing for the title of America's next drag superstar, participating in various challenges from singing to acting to walking the runway. The contestants are performing Drag Queens. Although Rusty Barrett describes Drag Queens as "almost always gay men" (313), this erases the identity of many of the contestants. Many of them identify as gay men, however a number of contestants also find themselves on the trans-spectrum, identify as non-binary, genderqueer, or as transsexual, sometimes already in transition. Here lies one of the biggest issues with the analysis of Drag: it might be very easy to see the contestants as men dressing up as women, but that would adhere to a binary that doesn’t always apply to Drag Queens.